2014
DOI: 10.3109/01480545.2014.968933
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flurbiprofen genotoxicity and cytotoxicity in rat bone marrow cells

Abstract: This study was performed to investigate cytogenetic effects of NSAID flurbiprofen which was used as active ingredient in some analgesic, antipyretic and anti-inflammatory drugs. Genotoxic effect of flurbiprofen was investigated using in vivo chromosome aberration (CA) test and random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) test. Also, oxidative stress potential of flurbiprofen was determined by measuring total oxidant and antioxidant level which occurred with flurbiprofen treatment in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…This is the first report mentioned about DNA protective effect of a NSAID. This results supports the findings about FLB's genotoxicity (Timocin & Ila, 2015;Timocin et al, 2016). This first report of RXM's DNA damaging and protection activity showed that RXM did not have damaging or protection activity on DNA.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is the first report mentioned about DNA protective effect of a NSAID. This results supports the findings about FLB's genotoxicity (Timocin & Ila, 2015;Timocin et al, 2016). This first report of RXM's DNA damaging and protection activity showed that RXM did not have damaging or protection activity on DNA.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study, FLB reduced mitotic index (cytotoxicity marker) (Carrano & Natarajan, 1988) for 12 and 24 h treatment periods in rat bone marrow cells. Also, this reduction was concentration dependent for 12 h (Timocin & Ila, 2015). In an another study, 200 mM FLB (48 h) lead to apoptosis in squamous cell carcinoma lines in vitro, inducing caspase-3 enzyme activity (Bock et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations